Blood and performance adaptations to individual training load in professional soccer players: a team study - Rago, V.; Leo, I.; Marrocco, A.; Izzo, R.; Filetti, C. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: The aim of this study was to describe seasonal changes in iron storage, hormonal status and functional capacity in relation to accumulated training load in a professional male soccer team. METHODS: Resting blood samples, countermovement jump (CMJ) and aerobic capacity (45-15 test) were collected over a 6-month period from the start of the preparatory period to the middle-season (E1 to E4) in a professional male soccer team (n=15 outfield players). External training load was regularly quantified using a wearable 10-Hz global positioning system. RESULTS: One player systematically showed reduced iron storage throughout the season (ferritin <110 µg/L, hemoglobin <14 g/dL). No significant differences in blood and performance parameters were observed throughout the season (P>0.05). However, accumulated total distance and high-intensity distance (above maximal aerobic speed) from E1 to E3 were negatively correlated to changes in hematocrit, hemoglobin and red blood cells (r=-0.85 to -0.67; P<0.05) and positively to changes in ferritin (r=0.63-0.69; P<0.05). Additionally, high-intensity distance covered between E1 and E3 was negatively correlated to changes in testosterone concentrations (r=-0.71 [95% CI -0.93; -0.15]; P=0.021). CONCLUSIONS: Resting blood parameters and functional capacity of male soccer players appeared to be stable throughout the early competitive period. However, iron storage and hormonal status are likely to be affected by accumulated high-intensity activity performed during practice and competition. Practitioners involved with GPS-based TL monitoring could consider the accumulated amount of high-intensity activity to inform medical staffs about possible changes in oxygen-carrying capacity and anaerobic overtraining.